2021
DOI: 10.17509/cd.v12i2.40304
|View full text |Cite
|
Sign up to set email alerts
|

Local Wisdom in Laro Ng Lahi as Foundation in Game-Based Pedagogy

Abstract: Filipino traditional games (Laro ng Lahi) are reflective of the lifestyle of a locality and form part of significant national heritage. Albeit modern technology seems to challenge the existence of Laro ng Lahi, these traditional games can actually be transformed to adapt the present demands of the cyberspace. Employing the hermeneutic phenomenology and educational research development, the author paired the past investigations with his observations though the use of Hermeneutic Cycle as guide. Data obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Students learn best when they can positively relate to lessons with these games as examples. It corroborates with the studies conducted by previous scholars(Avila, 2021;Barlizo & Osorno, 2022; Morales, 2015; Morales, 2016; Moro & Billote, 2023), who found that students stay motivated during the lesson with indigenous games integrated into the lesson.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Students learn best when they can positively relate to lessons with these games as examples. It corroborates with the studies conducted by previous scholars(Avila, 2021;Barlizo & Osorno, 2022; Morales, 2015; Morales, 2016; Moro & Billote, 2023), who found that students stay motivated during the lesson with indigenous games integrated into the lesson.…”
supporting
confidence: 91%
“…Thematic analysis was used to elicit and draw conclusions from the coded data. In particular, after the researchers determined the different perspectives of stakeholders, particularly the teachers (Agustin, 2020;Barlizo & Osorno, 2022;Booc et al, 2019;Cajetas-Saranza, 2020;Cerda, 2021;Morales, 2015;Mabborang et al, 2022;Moro & Billote, 2023;Mozar, 2020;Prestoza et al, 2020), students (Avila, 2021;Barlizo & Osorno, 2022;Booc et al, 2019;Morales, 2015), government officials (Mozar, 2020), and even others (or the authors themselves) (Almario, 2005;Cagas et al, 2022) and later make the coding, the data was analyzed thematically. Here, it was found that the Philippine traditional games can promote cultural heritage, facilitate convenient learning, and strengthen the foundation values, health, and socialization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It means that traditional Filipino games are useful in increasing students' science achievement. Avila [31] asserts that incorporating "Laro ng Lahi" or traditional games can help students develop knowledge and abilities for a certain course lesson.…”
Section: Discussionmentioning
confidence: 99%